Institutionalization of Community Engagement at African Universities - Mugabi, Henry (International Higher Education, 2015)
Since the establishment of the first university in Europe in the 11th century, the mission of the university has expanded from teaching to teaching, research, and service to, and engagement with, external communities. Although African universities are no exceptions to this mission, their community engagement function has not been fully developed and researched. Accordingly, the aim of this paper is to analyze, and offer suggestions regarding, institutionalization of community engagement at African universities.